Blended Learning at the Faculty of Philosophy in Kosovska Mitrovica and Why It Failed: A Case Study - Janković, Anita V (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Systematic implementation of the blended learning approach in teaching and learning of English as a foreign language was first initiated at the Faculty of Philosophy in Kosovska Mitrovica in October 2013 within the framework of the Tempus BLATT project, delivering the blended course of Contemporary English Language 1 for the first year students at the Department of English Language and Literature in two consecutive school years. The instructional design of the course presented a mixture of delivery modes and learning styles under the scope of strategically planned use of online learning tools fused with the features of the brick-and-mortar classroom. The aim of this paper is threefold: (1) to perform a review of available literature in search of a comprehensive list of success factors for the institutional adoption of blended learning in higher education as well as the resulting obstacles; (2) to measure conditions under which the blended learning was implemented at the Faculty against the found factors; (3) to present the results of the evaluation study on the quality of the course, the student satisfaction, and the teachers’ perceptions of the blended mode of delivery.